Biofeedback technology for stress management and self-regulation of athletes (2022)
With present technological advancement, the construct of stress management and self- regulation has received a new approach as this affects both psychological and physiological indices of athletes during training, competition, injury recovery and psychological wellbeing. The thought of biofeedback technology that makes use of instruments (electronic devices with electrodes and sensors) to assess, monitor, and feed psycho physiological information back to a person which is gaining recognition is to build a more complete tool to improve athlete’s performance and psychological wellbeing rather than replacing the traditional PST. In this perspective, the paper examined brief historical background of biofeedback in sports, meaning of biofeedback and biofeedback training, biofeedback modalities, stress management, self-regulation, biofeedback technology for stress management and self-regulation, two training models of Wingate 5-Step Approach (W5SA) and the Learning-Modification- Application (LMA) Approach. The author suggested that, sport scientists, sport psychologists and coaches could adopt biofeedback technology as a means to manage competitive stress and improve athlete’s self-regulation for great performance and optimal Health